Predictors of hazardous and harmful alcohol use among Nigerian Freshmen (2004)
Problem drinking among young persons is a concern among contemporary researchers. The present study examines the prevalence and the predictors of hazardous and harmful alcohol use among a sample of freshmen at the University of Ibadan Nigeria. Five hundred and forty freshmen were surveyed, of which 289 used alcohol. The effect of eighteen psychosocial variables on Alcohol Use Disorder Identification Test (AUDIT) scores was investigated using regression analysis. The results showed that, being a male freshman (r=0.78, p < 0.0005); coming from a polygamous home background (r = 0.59, p < 0.0 I); high levels of parents socio-economic status (r = -0.47, p < 0.0005); living with both parents (r= -0.24, p < 0.0005); mother working full time outside home (r=0.39. p < 0.005); increasing number of siblings (r= 0.35, p < 0.0005); living in urban cities (r = 0.38, P < 0.005); belonging to a social club (r = -0.46, p < 0.01); increasing religious activities (r = -0.51, P < 0.005); increasing parent child interaction (r= 0.72, p < 0.0 I); and low need for affiliation (r = -0.49, p < 0.0005) were found to be associated with hazardous and harmful alcohol use among the freshmen. When these eleven variables were entered into a stepwise multiple regression analysis to determine their relative predictive power to hazardous and harmful alcohol use among the freshmen, three variables; being a male (p < 0.0005); polygyny polygamy (p < 0.0053) and low need for affiliation (p < 0.0053) remained significant. There is a need to consider psychosocial factors in designing health educational programs for students on alcohol consumption.